2019
DOI: 10.15616/bsl.2019.25.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Classification of18F-Florbetaben Amyloid Brain PET Image using PCA-SVM

Abstract: Amyloid positron emission tomography (PET) allows early and accurate diagnosis in suspected cases of Alzheimer's disease (AD) and contributes to future treatment plans. In the present study, a method of implementing a diagnostic system to distinguish β-Amyloid (Aβ) positive from Aβ negative with objectiveness and accuracy was proposed using a machine learning approach, such as the Principal Component Analysis (PCA) and Support Vector Machine (SVM). 18 F-Florbetaben (FBB) brain PET images were arranged in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Before elucidating the design of a generative model in Section 2.4, we first defined the target model for which the images created from the generative model in this experiment will be trained. Previous studies [43,44] have shown that the performance of the ML/DL-based classification system for the Aβ distribution on FBB amyloid PET image data obtained from DAUH was 92.38% and 93.37%, respectively. Brain images generated using various modalities such as Magnetic Resonance Imaging (MRI), CT, and PET maintain spatial, and, depending on the conditions, temporal information of more than 3-dimensions.…”
Section: Target Model To Enhance With Generated Setmentioning
confidence: 97%
See 3 more Smart Citations
“…Before elucidating the design of a generative model in Section 2.4, we first defined the target model for which the images created from the generative model in this experiment will be trained. Previous studies [43,44] have shown that the performance of the ML/DL-based classification system for the Aβ distribution on FBB amyloid PET image data obtained from DAUH was 92.38% and 93.37%, respectively. Brain images generated using various modalities such as Magnetic Resonance Imaging (MRI), CT, and PET maintain spatial, and, depending on the conditions, temporal information of more than 3-dimensions.…”
Section: Target Model To Enhance With Generated Setmentioning
confidence: 97%
“…When evaluating PET images for the presence of FBB amyloid, the nuclear medicine physician makes a reading decision based on the contrast of gray matter observed through the axial plane of the FBB Aβ PET. Therefore, in a previous study [43,44,46], the BAPL score of a given FBB PET was estimated based on the Aβ distributions found at each axial level, also known as regional cortical tracer uptake (RCTU), instead of extracting the features from the 3D information according to the current process used by physicians.…”
Section: Target Model To Enhance With Generated Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is also recent work using them on automatic and semi-automatic segmentation algorithms in PET [ 6 , 7 ]. In one study, an AD diagnosis classifier using PCA and SVM was utilized after image dimension reduction of [ 18 F]Florbetaben brain PET images [ 8 ], and in another, images were classified according to amyloid deposition with an accuracy of 89% [ 9 ] using Visual Geometry Group (VGG) 16 [ 10 ], which is a well-known structure among convolutional neural networks (CNN) [ 11 , 12 ] that specializes in image feature extraction using deep learning technology.…”
Section: Introductionmentioning
confidence: 99%